Reproductive Life Span and Severe Hypoglycemia Risk in Postmenopausal Women with Type 2 Diabetes Mellitus - Soyeon Kang; Yong-Moon Park; Dong Jin Kwon; Youn-Jee Chung; Jeong Namkung; Kyungdo Han; Seung-Hyun Ko (Diabetes & Metabolism Journal, 2022)
Background Estrogen promotes glucose homeostasis, enhances insulin sensitivity, and maintains counter regulatory responses in recurrent hypoglycemia in women of reproductive age. Postmenopausal women with type 2 diabetes mellitus (T2DM) might be more vulnerable to severe hypoglycemia (SH) events. However, the relationship between reproductive factors and SH occurrence in T2DM remains unelucidated. Methods This study included data on 181,263 women with postmenopausal T2DM who participated in a national health screening program from January 1 to December 31, 2009, obtained using the Korean National Health Insurance System database. Outcome data were obtained until December 31, 2018. Associations between reproductive factors and SH incidence were assessed using Cox proportional hazards models. Results During the mean follow-up of 7.9 years, 11,279 (6.22%) postmenopausal women with T2DM experienced SH episodes. A longer reproductive life span (RLS) (≥40 years) was associated with a lower SH risk compared to a shorter RLS (<30 years) (adjusted hazard ratio [HR], 0.74; 95% confidence interval [CI], 0.69 to 0.80; P for trend <0.001) after multivariable adjustment. SH risk decreased with every 5-year increment of RLS (with <30 years as a reference [adjusted HR, 0.91; 95% CI, 0.86 to 0.95; P=0.0001 for 30–34 years], [adjusted HR, 0.80; 95% CI, 0.76 to 0.84; P<0.001 for 35–39 years], [adjusted HR, 0.74; 95% CI, 0.68 to 0.81; P<0.001 for ≥40 years]). The use of hormone replacement therapy (HRT) was associated with a lower SH risk than HRT nonuse. Conclusion Extended exposure to endogenous ovarian hormone during lifetime may decrease the number of SH events in women with T2DM after menopause.